The impact of social media on the financial decisions of students at Uganda Christian university - NDUHURA, JAZEL KENYONYOZI (Uganda Christian University, 2026)
This study investigates the impact of social media on the financial decisions of youth, focusing specifically on undergraduate students at Uganda Christian University (UCU). The research aims to address the modern conundrum in which tech-savvy youth, in a climate of aggressive social commerce, often display a high degree of financial mismanagement in favor of status spending in social media compared to basic necessities and savings. The main aim of the research is to determine if social commerce acts as a means of empowering youth financially or as a means of inducing financial imprudence. As such, an in-depth critical review of existing literature indicates an impactful relationship between algorithmic digital advertisement and impulsive consumption. Rooted in Social Learning Theory and Theory of Planned Behavior, the theoretical framework indicates how "performativity" in consumption and "fear of missing out" (FOMO) cultivate subjective norms that actively dissuade the culture of savings. Further still, existing literature indicates an unprecedented shift in financial power towards digital influencers who gamify risks in high-stakes speculations rather than conventional approaches to wealth accumulation. In terms of methodology, the study used a quantitative cross-sectional survey research design to solicit the status quo of the financial habits of the students. This was done by administering a questionnaire to a stratified random sample of 100 students at the UCU Main Campus using a fivepoint Likert scale. Using the SPSS software, the collected data was analyzed to determine the extent to which social media affects the behavior of the students in terms of finance by using descriptive statistics, the Pearson correlation coefficient, and linear regression analysis. The results were based on a 96% response rate, which established that: Inferential statistical tests were used to analyze the data, which established a strong positive correlation between targeted advertisements and impulse purchasing (r = 0.620). It also established a strong negative correlation, which indicated that increased peer pressure heavily diminishes the students' capacity to save (r = -0.480). Regression analysis results indicated that 46.2% of the total variance in the students' financial decisions can be explained by the social media factors. The study established that the digital environment functions as a catalyst for consumption and financial fragility rather than empowerment for UCU students. In order to combat these detrimental consequences, recommendations are proposed. These include the need for university management to incorporate digital financial hygiene into the foundation curriculum. Other recommendations are to promote peerto-peer saving advocacy through student guilds and to encourage the critical evaluation of financial influencers on the digital environment for the longterm financial well-being of the youth
Undergraduate